The pandemic in the North Atlantic: How COVID-19 has united a polarized micronation – and how well-known conflicts are still smouldering - Skorini, Heini í; Albinus, Herit (Politica, 2022)
The COVID-19 pandemic has illustrated the significance of popular support for – or resistance against – scientific and political authorities in a declared state of emergency. Based on quantitative and comparative surveys, the article examines popular attitudes to COVID-19-related issues in a democratic micronation within the Danish kingdom, the Faroe Islands. Furthermore, the article examines what demographic factors can explain popular support for the way public authorities have managed the pandemic as well as the willingness to be vaccinated. The article concludes that the COVID-19 pandemic has united the Faroese population across partisan, ideological and other demographic cleavages. However, the survey also finds that public opinion is a changeable phenomenon and that well-known cleavages such as political ideology, religion and age might still explain popular disagreements on COVID-19-related issues.